2012
DOI: 10.1136/bmj.e5310
|View full text |Cite
|
Sign up to set email alerts
|

A national early warning score for acutely ill patients

Abstract: A new standard to help identify patients in need of critical care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 7 publications
(5 reference statements)
3
113
0
1
Order By: Relevance
“…1 EWS are central to the concept of 'critical care without walls', delivered by nurse-led critical care outreach teams or physician-led medical response teams. 2 There are many types of EWS and a variety are used in the United Kingdom. 1 Some scoring systems are associated with patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…1 EWS are central to the concept of 'critical care without walls', delivered by nurse-led critical care outreach teams or physician-led medical response teams. 2 There are many types of EWS and a variety are used in the United Kingdom. 1 Some scoring systems are associated with patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A recent British Medical Journal editorial was subtitled 'A new standard should help identify patients in need of critical care'. 4 In many ways this misses the point of NEWS, simply because of the phrase 'critical care'. Implicit in this phrase are the separate departments and teams within the hospital that offer augmented levels of care.…”
mentioning
confidence: 99%
“…It was shown that qSOFA score has poor sensitivity and is a late indicator of clinical deterioration. The same study found that National Early Warning Score (NEWS-recommended by NICE guidelines, UK Sepsis Trust, Royal College of Emergency Medicine) which uses data that is equally accessible at the bed side as a having better sensitivity and specificity 17,18 .…”
Section: What Are the Limitations Of Sepsis 3?mentioning
confidence: 94%